Sosialisasi Kultur Pendukung Prekariat dalam Institusi Pendidikan - Edo Audre Kharnan Yudisda (Indonesian Journal of Sociology and Education Policy, 2017)
The precariat is a group of people who undergo unsafe conditions at work, which occurs due to the short tenure, minimal job protection, low stability of income and employment careers, and regulations that do not support the welfare of workers (Standing 2010). The results of the literature review of studies shows that the conditions of precariat phenomena are caused by structural aspects, namely changes in the global economic structure, which is capable of causing a change of culture and managerial significance of the company’s workers. These studies have not shown the culture encouraging people to become precariat is socialized separately in educational institutions as a producer of labor. Therefore this study is purposed to show the role of educational institutions in socializing and forming precariat culture among students. In this article I argue that the students internalize the precariat supporting culture in educational institutions through the rules and the school context. This study used a qualitative approach using in-depth interviews and observation to explore the process of socialization on students who form supporting precariat culture.